mKitchen™ towards Masyarakat Madani - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohd Ali, Noor Azian; Mohamadali, Noor Azizah; Abdul Aziz, Normaziah; Mahri, Nurhafizah; et al. (mKitchen KICT IIUM, 2023)
This book narrates the MADANI SCRIPT journey of empowering IIUM mKitchen™ Students with the 3Es (Employment, Empowerment, and Entrepreneurship). The students started the journey with in-class training on entrepreneurship, business model and plan development, digital marketing, and cash management. Then, the students had a cooking demonstration on several foods trained by trainers of mKitchen. This batch is fortunate to have a permanent space given by the university. The 40 years of sadaqah in funding for free food programmes are very valuable. In a poor society, sadaqah is an act of charity that is seen as an essential part of the social fabric. It refers to voluntary giving and can include providing financial assistance, food, clothing, or other items to those in need. The idea behind sadaqah is not only to provide aid but also to promote solidarity among members of the community. Helping others in their time of need encourages individuals to look out for each other and build strong relationships within their communities. Sadaqah also promotes a sense of responsibility towards those who are less fortunate and helps create a culture where everyone contributes what they can no matter how little it might be. mKitchen™ is a game changer that drives multiple sustainable development goals to give the highest values and benefits to the people in terms of economics, society, and environment. Meaningful teamwork in charity work involves a group of people coming together to collaborate and use their individual skills, talents, and resources to accomplish a common goal. The team should also strive for transparency regarding decision-making processes while maintaining an open dialogue with all stakeholders involved in the project. Finally, meaningful teamwork requires mutual trust among members so that everyone feels supported throughout the process of achieving common goals.